Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Văn học, 2004)
Nguyên Hồng; Bùi Hiển; Tô Hoài; Nguyễn Trọng Hứa; Băng Hồ; Hải Hồ; Trang Thế Hy; Lê Vĩnh Hoà; Trần Ninh Hồ; Tô Ngọc Hiến.